PENCEMARAN AIR SUNGAI TUK AKIBAT AIR LIMBAH DOMESTIK (STUDI KASUS KELURAHAN BENDAN NGISOR DAN KELURAHAN SAMPANGAN KECAMATAN GAJAH MUNGKUR KOTA SEMARANG) - L. A. Sasongko (Universitas Wahid Hasyim, 2008)
Tuk River has high potential to be polluted by domestic waste water because it passed along market area and residence. That condition is urgent to be concerned because the river empties near of Kaligarang River water taking spot which has been as drink water resources of PDAM (district enterprise of drinking water) Semarang City. Research purpose : (1) to evaluate water quality on Tuk River that caused by domestic waste water throwing include BOD, nitrate and phosphate parameter change; (2) to know the daily fluctuation of Tuk River water quality include BOD, nitrate and phosphate parameter. The research population of water quality included whole Tuk River water in Bendan Ngisor and Sampangan Village. Water sample were taken on four spot. Generally, The Tuk River was has more function as drainage channel than as water resource so debit, BOD, phosphate and nitrate more increasing from up river region to low river region. That condition was more damaged by many concrete drainage channels that makes domestic waste water infiltration not possible and the lack of open green space make the run-off flow directly to the water body. Total content of domestic waste water flow from Tuk River was indicated from content on spot D that has located at Tuk River empties which related directly with Kaligarang River. Generally, the peak of total content for a lot of domestic waste water indicator was attained on Saturday morning. It indicated that on this period there was many residents activity which produce domestic waste water. Keyword : domestic waste water, Tuk River